2014
DOI: 10.1177/160940691401300113
|View full text |Cite
|
Sign up to set email alerts
|

An African American Mother's Stories as T.M.I.: M.N.I., Ethics, and Vulnerability around Traumatic Narratives in Digital Literacy Research

Abstract: This article examines how an African American mother's affinity for digital tools relates to her telling of traumatic narratives, and how the very personal information contained in such narratives often problematizes the methodology of reporting qualitative research methods. These tensions include the concept of T.M.I. in qualitative research, as well as related ethical issues such as participant vulnerability, informed consent, and risks and benefits. This work addresses three key roles relevant to T.M.I.: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The professionals consulted at our workshop identified ethical considerations in this field to be of particular importance and interest, especially when dealing with sensitive topics such as sexual health and working with marginalised or vulnerable populations. However, only two of the included papers focussed specifically on the ethical considerations of digital storytelling (Ellison, 2014; Gubrium et al, 2014a); neither in the fields of sexual health or young people. The majority of other papers only briefly discussed ethical considerations.…”
Section: Resultsmentioning
confidence: 99%
“…The professionals consulted at our workshop identified ethical considerations in this field to be of particular importance and interest, especially when dealing with sensitive topics such as sexual health and working with marginalised or vulnerable populations. However, only two of the included papers focussed specifically on the ethical considerations of digital storytelling (Ellison, 2014; Gubrium et al, 2014a); neither in the fields of sexual health or young people. The majority of other papers only briefly discussed ethical considerations.…”
Section: Resultsmentioning
confidence: 99%
“…Solorzano and Yosso (2002) highlighted personal stories, other people’s stories, and composite stories, which make up counter-stories/narratives about education. Similar research has explored the dominant discourse about social and educational factors for African American male undergraduates at predominantly White universities (Harper, 2009), for Black youth in urban communities (Woodson, 2015), for teachers in urban schools (Milner, 2008) and community settings (Lazar, 2007; Seidl, 2007), for mothers’ narratives about their disabled children (Fisher & Goodley, 2007), for urban African American mothers’ traumatic narratives concerning digital literacy research (Lewis Ellison, 2014), for counter-stories from five queer multiparent families (Vaccaro, 2010), for parents’ counter-narratives about their children’s literacy development (Rogers & Brefeld, 2015), for building parent advocacy about their children’s education from eight African American and European American mothers (McKenna & Millen, 2013), and for teachers and parents who oppose high-stakes testing (Freeman, Mathison, & Wilcox, 2006; Malsbary, 2016). These studies demonstrated factors in which individuals’ perspectives were silenced or marginalized both in and out of educational institutions.…”
Section: Counter-storytellingmentioning
confidence: 99%
“…In Figure 1, Lewis Ellison captured Larnee's verbal and non-verbal talk as actions and still images to describe these activities. It was through such interactions that Lewis Ellison observed Larnee disassembling a computer, explaining how the motherboard had become a prominent focus and part of her self as a mother (Lewis, 2009(Lewis, , 2011Lewis Ellison, 2014). Study 2.…”
Section: )?mentioning
confidence: 99%